DEVELOPMENT OF AN ENVIRONMENTALLY FRIENDLY SANITATION SYSTEM IN TANJUNG PURA DISTRICT, LANGKAT REGENCY - Ario Darmanta Ginting; Abdi Sugiarto; Cut Nuraini (PT. Radja Intercontinental Publishing, 2025)
This study aims to explore the development of an environmentally friendly sanitation system that is in accordance with the social, economic, and environmental characteristics in Tanjung Pura District, Langkat Regency. Based on existing conditions that indicate low quality of sanitation management, this study identifies various models of sanitation systems that can be applied in the area, including community-based decentralized sanitation systems, communal wastewater treatment systems, and green technology. The results of the study indicate that community-based sanitation models and communal wastewater treatment are the most appropriate solutions to improve sanitation and environmental quality in Tanjung Pura District. The importance of community roles and collaboration between various stakeholders, such as government, private sector, and non-governmental organizations, are also emphasized as success factors in developing a sustainable sanitation system.